ANALISIS DAYA SAING USAHATANI PEMBESARAN IKAN LELE PETANI PEMODAL KECIL DI KECAMATAN RUMBAI PESISIR, KOTA PEKANBARU - Heriyanto (UIR Press, 2018)
ABSTRACT Indonesia is a country that has a level high enough fish production annually, submitted by the Minister of Fisheries and Maritime Affairs that Indonesia provides enough supply of fish to foreign countries. Indonesia was ranked second in the fish exporting country in the world after China. Based on the description in general, this study aims to: Analyze the competitiveness of enlargement catfish. As for the specifics, this study aims to 1) analyze know the characteristics of the farmers, 2) analyze the competitiveness of the business of enlarging catfish, 3) to analyze the impact of government policies on output and input in the business of enlarging catfish. This study is a survey in RumbaiPesisir sub-district Pekanbaru City with a sample size of 15 respondents. To answer the research objectives are analyzed descriptive statistics and analysis Policy Analysis Matrix (PAM). Based on the results of the research shows that the First: characteristics of the average farmer 41 years of age, low education, a farming experience of 8 years, an average of 0.19 hectares of land ownership. and the average number of family members of three people. Second: Enterprise's enlargement catfish in RumbaiPesisir sub-district Pekanbaru City on small investors have a competitive advantage which is characterized by catfish PCR <1 of 0.55 and a high comparative advantages characterized by DRCR <1 0.37. Third: government policy towards input subsidy in the form of tradable production facilities give benefits to business of enlarging catfish farmers RumbaiPesisir sub-district Pekanbaru City on the small investor farmers. Keywords: Competitiveness, Catfish, Input-Output, PAM Analysis.